TINGKAH LAKU INDUK BETINA SELAMA PROSES PENGERAMAN TELUR DAN PERKEMBANGAN LARVA LOBSTER PASIR (Panulirus homarus Linneaus, 1785) - M. Junaidi Junaidi; N. Cokrowati; Z. Abidin (Jurnal Akuatika, 2011)
This study aims to determine the behavior of female brooodstock on sipny lobsters when incubating their eggs until they hatch and the larvaldevelopment. Reared of the female broodstock and hatch eggs made at the aquarium. Observation of broodstock behavior during egg incubation with visualization in the form of photos and video. Eggs that have hatched transferred to larval rearing container and given a feed Chaetocerossp, Tetraselmissp and Artemiasalina. Observation of larval development  by using a microscope and visualized in the form of photographs.Broodstock  behavior during lay eggs are always bent and telson body covering eggs, and when the eggs begin to hatch pereiopod always shaken. Filosoma larval growth stage I to the next level, marked by the addition of setae on the pereiopodThe 1st and 2nd pereiopod, where from 5 pairs at the level I to 6 pairs at level II. At level III, increased to 7 pairs of setae, and there are 3 pairs of setae on the pereiopod the 3rd and 4th pereiopod began to grow. Filosoma larval development is only to a level III, with a time of maintenance in the laboratory for 27 days.